2019
DOI: 10.1093/zoolinnean/zlz157
|View full text |Cite
|
Sign up to set email alerts
|

Orogeny, sympatry and emergence of a new genus of Alpine subterranean Trechini (Coleoptera: Carabidae)

Abstract: Despite two centuries of research in European subterranean habitats, which resulted in descriptions of numerous obligate subterranean beetle species, the role of ecological differentiation in speciation of subterranean beetles remains understudied. Discovery of a new genus and a species of Alpine subterranean Trechini beetles, Petraphaenops unguiculatus gen. & sp. nov., enables us to question the reasons for its morphological and ecological divergence. Multilocus, time-calibrated phylogeny and extensive mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Faille et al (2011;2013; hypothesized that the Duvalius lineage, consisting of eight "genera," was monophyletic. Our phylogenies are consistent with a large Duvalius clade (Delić et al, 2020;Faille et al, 2013Faille et al, , 2018 and confirm non-monophyly of the genera nested within as found in previous analyses (Delić et al, 2020;Faille et al, 2013Faille et al, , 2018. In other words, Duvalius is paraphyletic with respect to these other genera.…”
Section: Zagros Cladesupporting
confidence: 90%
See 2 more Smart Citations
“…Faille et al (2011;2013; hypothesized that the Duvalius lineage, consisting of eight "genera," was monophyletic. Our phylogenies are consistent with a large Duvalius clade (Delić et al, 2020;Faille et al, 2013Faille et al, , 2018 and confirm non-monophyly of the genera nested within as found in previous analyses (Delić et al, 2020;Faille et al, 2013Faille et al, , 2018. In other words, Duvalius is paraphyletic with respect to these other genera.…”
Section: Zagros Cladesupporting
confidence: 90%
“…We obtained original, four marker sequences (see below) of three Muilwijk & Felix, 2008), and D. hetschkoi matilei (one specimen, previously published in Deuve, 2000) were used for morphological comparison with the above three species (Appendix 1). From GenBank, we additionally mined the same four marker sequences for nine genera that are hypothesized to be nested within the Duvalius clade (Delić et al, 2020;Faille et al, 2013): In total, we selected sequences of 43 species of Duvalius, 11 species of Anophthalmus, and for representatives of Agostina (1), Aphaenopidius…”
Section: Taxon Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no seceding characteristics in the genital morphology between the two geographical Nemaspela groups, but perhaps some external morphology features matter. Generally, the external morphology is of rather minor value in considering relations among the species in question, since interspecific competition may significantly influence the morphology of closely related animals (Fišer et al 2012;Vergnon et al 2013;Delić et al 2019), and convergent adaptation of distantly related species is common in the subterranean habitat (Derkarabetian et al 2010;Pipan & Culver 2012;Delić et al 2017). However, N. femorecurvata is the only species in the eastern Nemaspela group missing the male cheliceral apophysis, which is a normal condition in both Balkan species, N. ladae and N. borkoae sp.…”
Section: Discussionmentioning
confidence: 99%
“…The area has also been recognized as globally unique and as a hotspot for richness in subterranean species (Culver & Sket 2000;Culver et al 2006); many new species have been discovered and scientifically described in the last two decades. In recent times, improvements in caving equipment and techniques have enabled access to deeper caves and allowed more time for fauna collection, along with the discovery of new species (e.g., Lukić et al 2010;Andersen et al 2016;Antić 2018;Delić et al 2019;Trontelj et al 2019).…”
Section: Introductionmentioning
confidence: 99%